Impact of Metabolic Activity in Hepatocellular Carcinoma: Association With Immune Status and Vascular Formation. Issue 7 (26th March 2021) - Itoh, Shinji; Yoshizumi, Tomoharu; Kitamura, Yoshiyuki; Yugawa, Kyohei; Iseda, Norifumi; Shimagaki, Tomonari; Nagao, Yoshihiro; Toshima, Takeo; Harada, Noboru; Kohashi, Kenichi; Baba, Shingo; Ishigami, Kousei; et al.
Abstract : We evaluated the prognostic value of fluorine‐18 fluorodeoxyglucose ( 18 F‐FDG) positron emission tomography/computed tomography (PET/CT) in hepatocellular carcinoma (HCC). Their association with programmed death ligand 1 (PD‐L1) expression and vascular formation was further investigated. In this retrospective study, using a database of 418 patients who had undergone 18 F‐FDG PET/CT before hepatic resection for HCC, immunohistochemical staining of PD‐L1, clusters of differentiation (CD) 8, CD68, and CD34 was performed. Patients with a high maximum standardized uptake value (SUVmax) on 18 F‐FDG PET/CT showed a significantly worse recurrence‐free survival (RFS) (hazard ratio [HR]: 1.500; 95% confidence interval [CI]: 1.088‐2.069; P = 0.0133) and overall survival (OS) (HR: 2.259; 95% CI: 1.276‐4.000; P = 0.0052) than patients with a low SUVmax. Logistic regression analysis showed that a high SUVmax in HCC was significantly associated with PD‐L1‐positive expression (odds ratio: 4.407; 95% CI: 2.265‐8.575; P < 0.0001). SUVmax values of HCC were associated with intratumoral CD8‐positive T‐cell counts ( P = 0.0044) and CD68‐positive macrophage counts ( P = 0.0061). Stratification based on SUVmax, PD‐L1 expression, and the vessels that encapsulate tumor clusters (VETC) status was also significantly associated with RFS and OS. SUVmax, VETC, and PDL1 expression were independently predictive of survival on multivariable analysis. Conclusion: Our large cohort study showed that a high SUVmax on 18 F‐FDG PET/CT is associated with a poor clinical outcome and PD‐L1 expression in patients with HCC. Additionally, stratification of patients based on the combination of SUVmax, PD‐L1 expression, and the VETC status predicts poor clinical outcome.